Relationship between husband's support and wife's stress level after giving birth to their first child - Tiara Puspa Aldita; Verlanda Yuca (Jurnal Neo Konseling, 2022)
The husband's support is needed by the wife during pregnancy and after giving birth. Where this support is needed by the wife both financially and emotionally, to reduce the stress of the wife after giving birth the husband can provide emotional support, appreciation and affection as well as information and positive advice needed by the wife after giving birth. Factors that can cause stress to the wife include psychological and social factors, worries about not having experience, worries about whether the child will grow up well and also concerns about whether they can carry out their role as mothers well. This study aims to describe the husband's support, the wife's stress level after giving birth to her first child, and the relationship between husband's support and the wife's stress level after giving birth to her first child. This type of research is a quantitative study with a correlational approach, the population in this study was 246 people from clinics and health centers with a total sample of 92 people. The sampling technique used was purposive sampling. The instrument used is a scale of husband's support and wife's stress which is processed using the percentage technique. To see the relationship between husband and wife's support after giving birth to their first child, correlational techniques were used which were processed using SPSS 20.0.0. The findings of this study indicate that: (1) husband's support is in the low category, (2) wife's stress is in the high category and (3) there is a positive and significant relationship between wife's stress and husband's support.